Action-control as predictors of learning-related achievement emotions - Matti, Christopher Bernard L. (Animo Repository, 2008)
The present study investigated whether the factors of action control (disengagement, persistence, initiative, preoccupation, hesitation, volatility) can predict students' learning-related achievement emotions. These factors of action control are classified into action orientation and state orientation, while the achievement emotions are composed of the eight learning-related emotions: enjoyment, hope, pride, anger, anxiety, shame, hopelessness, and boredom. The relationship between action control and achievement emotions was based on action control theory by Kuhl (1984). It was hypothesized in the study that the factors of action and state orientation as predictors can vary depending on the kind of academic emotions predicted. The instruments used were the Action Control Scale (ACS-90) and the Achievement Emotions Questionnaire (AEQ). The Multiple Regression Analysis was used to determine whether the action and state orientation factors will significantly predict the achievement emotions. Results show that there is a positive relationship between the factors of action orientation and positive emotions, and that there is also a positive relationship between the factors of state orientation and negative emotions.